Pengaruh Volume Penjualan dan Harga Jual Terhadap Profitabilitas Pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023 - Pratama, Ramadhan Indi; Hasibuan, Thezar Fiqih Hidayat (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study describes the rice sub-sector companies listed on the Indonesia Stock Exchange in 2020-2023.The purpose of this study is to determine the influence of sales volume and selling price on profitability in rice sub-sector companies listed on the Indonesia Stock Exchange in 2020-2023. The sample used in this study is 32 data from financial statements and annual reports for the 2020- 2023 period. The classic assumption test used in this study is by using the normality test, multicollinearity test, heterokedasticity test and autocorrelation test. The data analysis used to test the hypothesis is using multiple linear regression analysis techniques. Based on the results of this study, it shows that (1) Sales Volume partially has a positive and significant effect on Profitability, shown by a tcount value of 3.145 a ttable value of 2.048 with a significance value of 0.004 0.05; (2) Selling Price partially does not have a positive and significant effect on Profitability, shown by a tcal value of 0.790 a ttable value of 2.036 with a significance value of 0.436 0.05; (3) Sales Volume and Selling Price simultaneously affect Profitability, shown by the value of Fcal 5.017 Ftable 3.25 with a significance of 0.013 0.05.